P61 SARS-CoV-2 vaccine safety in adolescents with inflammatory rheumatic and musculoskeletal diseases and adults with juvenile idiopathic arthritis: data from the EULAR COVAX physician-reported registry. (28th September 2022) - Lawson-Tovey, Saskia; Machado, Pedro; Strangfeld, Anja; Mateus, Elsa; Gossec, Laure; Carmona, Loreto; Raffeiner, Bernd; Bulina, Inita; Clemente, Daniel; Zepa, Julija; Rodrigues, Ana; Mariette, Xavier; et al.
Abstract: Introduction/Background: There is a lack of data on Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) vaccination safety in children and young people (CYP) with rheumatic and musculoskeletal diseases (RMDs) as they were excluded from initial vaccine trials. Vaccination guidance is based on data from adults with or CYP without RMDs. Description/Method: Our objective was to describe the safety of SARS-COV-2 vaccination in adolescents with inflammatory RMDs and adults with JIA. We described patient characteristics, flares, and adverse events in adolescent cases under 18 with inflammatory RMDs and adult cases aged 18 or above with JIA submitted to the European Alliance of Associations for Rheumatology (EULAR) COVAX registry. Discussion/Results: Thirty-six adolescent cases were reported from 4 countries, mostly female (58%) with JIA (42%: 28% non-systemic JIA, 14% systemic JIA) and a median age of 15 [IQR: 14.5, 17]. Most were in remission (64%) or had minimal (22%) disease activity at the time of vaccination. Over half of the adolescent group (56%) reported early reactogenic-like AEs. One mild polyarthralgia flare and one serious AE of special interest (malaise) were reported. No CYP reported SARS-CoV-2 infection post-vaccination. No cases of paediatric inflammatory multi-system syndrome or myocarditis adverse events were reported. Seventy-four adult JIA cases were reported from 11 countries; 73% were female with a median age of 26 [IQR: 23, 31]. Eight-five percent had ns-JIA and 15% had s-JIA. Almost two thirds (62%) reported early reactogenic-like AEs and two flares were reported (mild polyarthralgia and moderate uveitis). No serious AEs of special interest were reported among adults with JIA. Three 20-30 year old females were diagnosed with SARS-CoV-2 post-vaccination; all fully recovered. Key learning points/Conclusion: In this observational registry dataset, SARS-CoV-2 vaccines appeared safe in adolescents with RMDs and adults with JIA, with a low frequency of disease flares, serious AEs, and SARS-CoV-2 re-infection seen in both populations.